2022
DOI: 10.1002/hyp.14564
|View full text |Cite
|
Sign up to set email alerts
|

Conservative solute transport processes and associated transient storage mechanisms: Comparing streams with contrasting channel morphologies, land use and land cover

Abstract: Land use within a watershed impacts stream channel morphology and hydrology and, therefore, in‐stream solute transport processes and associated transient storage mechanisms. This study evaluated transport processes in two contrasting stream sites where channel morphology was influenced by the surrounding land use, land cover, climate and geologic controls: Como Creek, CO, a relatively undisturbed, high gradient, forested stream with a gravel bed and complex channel morphology, and Clear Creek, IA, an incised, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
(125 reference statements)
4
6
0
Order By: Relevance
“…In our study site, 𝜏 𝑡𝑠 decreased one order of magnitude from round 1 to round 2, and were comparable to the range of values observed in other studies involving forested mountain streams(Valett et al 1996;Hall et al 2002). Due to the geomorphology of the stream, which is characterized by steep longitudinal and valley slopes, pool and riffle sequences, and shallow bedrock, transient storage was expected to occur mainly in the main channel(Fields and Dethier 2019;Barnhart et al 2021;Emanuelson et al 2022). As flow receded from round 1 to round 2, we observed the disconnection of in-stream pools contributing to transient storage, which explains the direct correlation between discharge and transient storage timescales.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…In our study site, 𝜏 𝑡𝑠 decreased one order of magnitude from round 1 to round 2, and were comparable to the range of values observed in other studies involving forested mountain streams(Valett et al 1996;Hall et al 2002). Due to the geomorphology of the stream, which is characterized by steep longitudinal and valley slopes, pool and riffle sequences, and shallow bedrock, transient storage was expected to occur mainly in the main channel(Fields and Dethier 2019;Barnhart et al 2021;Emanuelson et al 2022). As flow receded from round 1 to round 2, we observed the disconnection of in-stream pools contributing to transient storage, which explains the direct correlation between discharge and transient storage timescales.…”
supporting
confidence: 89%
“…Our results indicate that the transformation of Raz (𝜆 𝑅𝑎𝑧 ) was directly and moderately correlated with the transient storage timescale (𝜏 𝑡𝑠 ), as other studies on reactive transport have shown (Valett et al 1996 (Zarnetske et al 2007;Schmid et al 2010), 𝜏 𝑡𝑠 in our study site increased with 𝑄 because the geomorphology of the channel and the valley favored in-stream transient storage in pools (Jackson et al 2012(Jackson et al , 2013(Jackson et al , 2015, and the metabolically active biofilms available there may have prompted the transformation of Raz (Haggerty et al 2014;Peralta-Maraver et al 2018). Consistently, when stream flows recede in these types of streams, the subsequent disconnection of parts of the channel causes a decline in transient storage and metabolism (Covino et al 2010a;Emanuelson et al 2022). Hall et al (2002) found similar results in a study of thirteen streams, where changes in stream width and depth primarily drove variations in transient storage timescales.…”
Section: Raz Transformation (A Proxy For Respiration) As a Function O...supporting
confidence: 74%
See 2 more Smart Citations
“…Thus, in addition to assessment of marginal mass recovery, we strongly recommend additional care is given to calculation of discharge. This could be realized by making discharge measurements independently of the tracer (e.g., via velocity gauging or co‐location a station with an established stream gauge), building a stage‐discharge relationship from several replication dilution gauging experiments, using multiple in‐stream sensors to validate complete mixing (e.g., Clow & Fleming, 2008), or otherwise assessing uncertainty in discharge and propagating that through calculations (Emmanuelson et al., 2022; Ward, Wondzell, et al., 2019). Any error in study of an individual segment may propagate through the analysis, and small errors could be amplified in the convolution of reaches to represent study segments.…”
Section: Discussionmentioning
confidence: 99%